Stationary/Non-Stationary Modelling for Extreme Value Distribution: Analysis of Rainfall Annual Maxima in Italy in a Climate Change Context - Davide Luciano De Luca; Benedetta Moccia; Fabio Russo; Francesco Napolitano (Environmental Sciences Proceedings, 2022)
In this paper, EXTRASTAR software (EXTRemes Abacus for STAtistical Regionalization) is illustrated, which provides a general framework for extreme value analysis, specifically for Annual Maxima (AM) time series. The proposed methodology represents a useful and quick approach to carry out onsite and regional statistical investigations of extreme events, which is also suitable for climate change scenarios. EXTRASTAR was tested with the AM time series at daily resolutions for the entire Italian rain gauge network by implementing EV1 (Extreme Value Type I), GEV (Generalized Extreme Value) and TCEV (Two-Components Extreme Value) probability distributions.